Resilience, Academic Stress, and Mental Well-Being Among Senior High School Students: Basis for a School-Based Mental Health Program - Corina Brenda M. Binondo (Journal of Counseling and Educational Research, 2026)
This study examined the relationships among resilience, academic stress, and positive mental well-being among Senior High School (SHS) students at Elizabeth Seton School and used the findings as a basis for developing a school-based mental health program. A mixed-methods research design was employed, combining a quantitative descriptive-correlational approach with a qualitative interview component. The quantitative phase involved 162 SHS students from the STEM, ABM, and HUMSS strands who participated through total enumeration sampling, while 10 students participated in semi-structured interviews through convenience sampling. Quantitative data were collected using the Perception of Academic Stress Scale (PAS), Warwick–Edinburgh Mental Well-being Scale (WEMWBS), and Resilience Scale (RS-23). Frequencies, percentages, weighted means, standard deviations, and Spearman's rank-order correlation were used to analyze the quantitative data, while thematic analysis was used to examine the qualitative interviews. The findings showed that students experienced high academic stress (M = 3.44, SD = 1.08), moderate positive mental well-being (M = 3.24, SD = 1.11), and moderate-to-high resilience (M = 5.06, SD = 1.49). Resilience had a weak positive but statistically non-significant relationship with academic stress (ρ = .136, p = .082), whereas it had a strong positive and statistically significant relationship with positive mental well-being (ρ = .745, p < .001). Qualitative findings highlighted academic overload, parental and societal expectations, limited rest, peer and family support, religious or spiritual coping, goal-focused persistence, disengagement, and technology use as important aspects of students' experiences. Overall, the findings suggest that resilience should not be viewed as a mechanism that necessarily reduces academic stress but may be more closely associated with students' positive mental well-being. The findings served as the basis for a proposed school-based mental health program integrating academic stress management, resilience-building, positive mental well-being promotion, and healthy coping strategies.